Pengaruh Kualitas Layanan dan Kepuasan Terhadap Loyalitas Mahasiswa (Studi Kasus Program Pascasarjana Fakultas Ekonomi dan Bisnis Universitas Airlangga) - Windasari Windasari; Soedjarwo Soedjarwo; Toho Cholik Mutohir (Universitas Kristen Satya Wacana, 2021)
Higher education institutions need to reform the organization culture of a bureucratic university become a corporate university. Education will be oriented towards high academic quality, service quality, and as well as student satisfaction. The purposes of this study are to measure and determine the effect of service quality and satisfaction on student loyalty in higher education sector. Data collection technique is done by distributing questionnaires with 5-point likert scale. There are 151 students chosen using cluster random sampling. The validity test used factor analysis. Data analysis technique was done using Structural Equation Modeling (SEM) with the help of the AMOS version 21.0 program. The result of the research shows that service quality and satisfaction simultaneously affect student loyalty.